Viral marketing analysis and evaluation: the case of the Greek consumer market. (2016) - Rouva, Eleni; Lalou, Panagiota; Skordoulis, Michalis; Chalikias, Miltiadis
The aim of the present study is to focus on the evaluation of viral marketing as a means of promoting goods and services within the Greek consumer market. The study focuses on consumer attitudes and reactions towards viral marketing practices in order to contribute to a better understanding of consumers' behaviour. The major findings indicate that viral marketing is on the rise among Greek companies due to technology development, low cost and its immediacy in transmitting the message. All three explored media of viral marketing, i.e., email, social media and audio-visual means, are of equal importance and equal use among viral marketers and users.